Possible involvement of sialidase and sialyltransferase activities in a stage-dependent recycling of sialic acid in some organs of type 1 and type 2 diabetic rats - Erhabor, Osas Graham; Obochi, Peter; Isah, Murtala Bindawa; Usman, Mohammed Aliyu; Umar, Ismaila Alhaji; Simelane, Mthokozisi B. C.; Shuaibu, Mohammed Nasir; Islam, Md. Shahidul; Ibrahim, Mohammed Auwal (Frontiers in Endocrinology, 2024)
Background: Type 1 (T1D) and type 2 (T2D) diabetes lead to an aberrant metabolism of sialoglycoconjugates and elevated free serum sialic acid (FSSA) level. The present study evaluated sialidase and sialyltranferase activities in serum and some organs relevant to diabetes at early and late stages of T1D and T2D.Methods: Sialic acid level with sialidase and sialyltransferase activities were monitored in the serum, liver, pancreas, skeletal muscle and kidney of diabetic animals at early and late stages of the diseases.The FSSA and activity of sialidase in the serum were significantly increased at late stage of both T1D and T2D while sialic acid level in the liver was significantly decreased in the early and late stages of T1D and T2D, respectively. Furthermore, the activity of sialidase was significantly elevated in most of the diabetes-relevant organs while the activity of sialyltransferase remained largely unchanged. A multiple regression analysis revealed the contribution of the liver to the FSSA while pancreas and kidney contributed to the activity of sialidase in the serum.We concluded that the release of hepatic sialic acid in addition to pancreatic and renal sialidase might (in)directly contribute to the increased FSSA during both types of diabetes mellitus.